The perceived needs-access gap for health services among persons with disabilities in a rural area within South Africa - Vergunst, Richard; Swartz, Leslie; Hem, Karl-Gerhard; Eide, Arne Henning; Mannan, Hasheem; MacLachlan, Malcolm; Mji, Gubela; Schneider, Marguerite (Disability and rehabilitation, 2019)
Purpose: Health should be a universal phenomenon. However, little is known about the relationship between disability status and health issues - particularly in rural areas. This study looks at health issues of persons with disabilities in Madwaleni, a rural impoverished area in South Africa in 2011, and compares them to persons with no disabilities. Materials and Methods: Standardized questionnaires were used in the survey to assess disability and health status. The sample comprised of 773 individuals - 322 persons with disability and 451 comparisons (without disability) - covering 527 households. Children under the age of five were excluded from the sample. We used purposive sampling. Results and Conclusion: This study found that persons with disabilities have poorer reported health outcomes than persons with no disabilities. There is also an association between disability severity and mental health issues as assessed by the GHQ-12. A significantly higher percentage of persons with disability did not get health care when needed. Persons with disabilities also have less favorable attitudes toward competence of health care workers. This study has shown greater health needs and less satisfaction with services, which strongly indicates insufficient access for persons with disabilities in a rural impoverished are within South Africa. Implications for rehabilitation Persons with disabilities in rural South Africa have poorer reported health outcomes. Persons with disabilities have less favorable attitudes towards competence of health care workers in rural South Africa. Better access to health care for persons with disabilities is needed in rural South Africa.
Keywords: lidé; zdravotnické služby - potřeby a požadavky; výsledek terapie; Adult; Jihoafrická republika; Attitude to Health; Persons with Disabilities; Female; průzkumy a dotazníky; posuzování pracovní neschopnosti; Health Services Needs and Demand; Humans; Patient Preference; Rural Population; South Africa; pacientova volba; Disability Evaluation; Health Services Accessibility; venkovské obyvatelstvo; mužské pohlaví; dostupnost zdravotnických služeb; duševní zdraví; ženské pohlaví; Treatment Outcome; Male; Mental Health; postižení; postoj ke zdraví; dospělí; Surveys and Questionnaires